The Thought Remolding Campaign of the Chinese Communist Party-state - Hu Ping (Amsterdam University Press, 2012)
In its comprehensive analysis of a wide range of primary and secondary sources in both Chinese and Western languages, this authoritative work stands as the definitive study of the theory, implementation and legacy of the Chinese Communist Party's thought-remolding campaign. This decades-long campaign involved the extraction of confessions from millions of Chinese citizens suspected of heterodoxy or disobedience to party dictates, along with their subjection to various forms of "re-education" and indoctrination. Hu Ping's carefully structured overview provides a valuable insider's perspective, and supersedes the previous landmark study on this vastly interesting topic.